2021
DOI: 10.1111/den.14194
|View full text |Cite
|
Sign up to set email alerts
|

Oral sulfate solution versus low‐volume polyethylene glycol for bowel preparation: Meta‐analysis of randomized controlled trials

Abstract: Background and Aims Oral sodium sulfate (OSS) solution and low‐volume polyethylene glycol‐based solutions are two of the more common low‐volume purgatives used as colonoscopy preparations. Data on how these different low‐volume solutions compare are mixed. Our aim was to conduct a meta‐analysis of randomized controlled trials (RCTs) to compare OSS with low‐volume polyethylene glycol solutions (PEG) plus ascorbic acid (PEG + Asc) solution with respect to (i) satisfactory bowel preparation, (ii) excellent bowel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…18,19 However, it is unclear whether OSS can ultimately increase PDR and ADR, although several studies have demonstrated that OSS has comparable or better quality of bowl preparation than PEG formulations and has acceptable safety. 14,22,23 In this meta-analysis, by pooling the eight RCTs, we first revealed that OSS for bowel preparation was associated with a significantly increased PDR and ADR during colonoscopy, which suggested that OSS might be an efficacious regimen for patients scheduled for a colonoscopy. Additionally, from the result of the analysis of the bowel preparation score, it was suggested that OSS significantly improved bowel preparation.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…18,19 However, it is unclear whether OSS can ultimately increase PDR and ADR, although several studies have demonstrated that OSS has comparable or better quality of bowl preparation than PEG formulations and has acceptable safety. 14,22,23 In this meta-analysis, by pooling the eight RCTs, we first revealed that OSS for bowel preparation was associated with a significantly increased PDR and ADR during colonoscopy, which suggested that OSS might be an efficacious regimen for patients scheduled for a colonoscopy. Additionally, from the result of the analysis of the bowel preparation score, it was suggested that OSS significantly improved bowel preparation.…”
Section: Discussionmentioning
confidence: 91%
“…An OSS regimen was associated with an increased excellent bowel preparation because the reduced volume may be more acceptable and tolerable; 48 however, a previous meta-analysis revealed a higher risk of nausea and vomiting in patients consuming the OSS regimen. 23 Currently, the definitive reasons for this result remain unknown; however, an unpleasant taste and flavor caused by the sulfate component has been suggested as a possible reason. 20,21 Trial sequential analysis, 53 which was conducted by TSA software 0.9.5.10 Beta (Copenhagen Trial Unit, Centre for Clinical Intervention Research, Rigshospitalet, Copenhagen, Denmark, https://www.ctu.dk/tsa), was used to further examine whether a definitive conclusion could be obtained for the risk of nausea and vomiting based on the results of a previous meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta‐analysis of multiple randomized controlled trials (RCTs) comparing OSS with PEG + ASC elucidated that OSS for bowel preparation increases the rate of excellent bowel preparation (50.6% vs. 42.6%) in patients at low risk of inadequate bowel preparation. However, OSS was associated with a significantly increased risk of nausea (38.5% vs. 29.4%) and vomiting (10.8% vs. 4.7%) compared to PEG + ASC 5 …”
mentioning
confidence: 91%